Performance of an Automatic Dose Control System for CT: Patient Studies - Stumpp, P.; Gosch, D.; Kühn, A.; Sorge, I.; Weber, D.; Lehmkuhl, L.; Kahn, T.; Nagel, H. D. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2013)
Purpose: To study the effect of an automatic dose control (ADC) system with adequate noise characteristic on the individual perception of image noise and diagnostic acceptance compared to objectively measured image noise and the dose reductions achieved in a representative group of patients.Materials and Methods: In a retrospective study two matched cohorts of 20 patients each were identified: a manual cohort with exposure settings according to body size (small – regular – large) and an ADC cohort with exposure settings calculated by the ADC system (DoseRight 2.0™, Philips Healthcare). For each patient, 12 images from 6 defined anatomic levels from contrast-enhanced scans of chest and abdomen/pelvis were analyzed by 4 independent readers concerning image noise and diagnostic acceptance on a five-point Likert scale and evaluated for objectively measured image noise. Radiation exposure was calculated from recorded exposure data. Results: Use of the ADC system reduced the average effective dose for patients by 36 % in chest scans (3.2 vs. 4.9 mSv) and by 17 % in abdomen/pelvis scans (7.6 vs. 8.3 mSv). Average objective noise was slightly lower in the manual cohort (11.1 vs. 12.8 HU), correlating with a slightly better rating in subjective noise score (4.4 vs. 4.2). However, diagnostic acceptance was rated almost equal in both cohorts with excellent image quality (4.6 vs. 4.5).Conclusion: Use of an ADC system with adequate noise characteristic leads to significant reductions in radiation exposure for patients while maintaining excellent image quality.
Keywords: abdomen; thorax; CT; physics; radiation safety